Ferulic acid production from banana stem waste : optimization - Thor, Ee Su (2014)
Ferulic acid is a compound well known for its anti-inflammatory and antioxidant properties, which is widely used in the food and cosmetic industry. The main objective of this study was to optimize the ferulic acid production from banana stem waste (BSW) by soil-mixed culture. Optimization of ferulic acid production was assisted by Central Composite Design (CCD). Previous screening studies have employed five processing parameters, viz. temperature, agitation speed, substrate-to-inoculum ratio, water-to-banana stem waste ratio and incubation time. It has been identified that the water-to-banana stem waste ratio and time factor are the most vital parameters. Consequently, the effect of time on ferulic acid production was studied in batch culture at duration ranging from 12 to 36 h and water-to-banana stem waste ratios of 0.5:1 to 1.5:1. The determination of ferulic acid was performed by High Performance Liquid Chromatography (HPLC). In addition, Design Expert software v 8.0.6 was used to design the experiment and analyse the obtained experimental data. The optimum condition obtained from this study is 1.1: 1 ratio of water-to-banana stem waste and incubation time of 27 hours. The yield of ferulic acid from this experiment was 1.17 mg FA/ g dry BSW which was lower than findings from other researchers such as Webber (2004) (21 mg phenolics/ g HDRB), Aybastier et. al.(2013) (82.12 mg phenolics/ g dried plant) and Salleh et. al. (2011) (8.17 mg FA/g paddy straw). Result from this work may be useful to optimize the ferulic acid in large scale production from BSW